Effectiveness of Cardiac Rehabilitation Instructional Program on Knowledge and Health-related Quality of Life for Patients Undergone Coronary Artery Bypass Graft Surgery - Isam, Safad Riyadh; Hassan, Hakima Shakir (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): Determination of effectiveness of cardiac rehabilitation instructional program on knowledge and health-related quality of life for patients undergone Coronary Artery Bypass Graft Surgery and to find out the relationship between knowledge and health-related quality of life of patients and their socio-demographic and clinical characteristics. Methodology: A pre-experimental design (one group, pretest- posttest) was carried out from 8th August, 2022 to 10th January, 2023. A non-probability purposive sample of (50) patients undergone coronary artery bypass graft surgery at Iraqi center for heart diseases. The questionnaire and the program contents’ validity was determined by a panel of (18) experts to evaluate their clarity, relevance, and appropriateness for the accomplishment of the study.The reliability of questionnaire was assessed using Cronbach alpha reliability to estimate its internal consistency. Correlation coefficient of (0.867) was determined which is acceptable. Patients were asked to fill the three questionnaires before applying the instructional program (pre-test), then the program has been presented and discussed through (4) sessions. After one month, patients were asked to refill the forms (post-test) to determine the effectiveness of the CR program. Descriptive and inferential data were analyzed by using: frequency, percentage, mean of score, standard deviation and paired t test.Results: The patient’s knowledge about cardiac rehabilitation and health-related quality of life before applying the program were poor in most items, while their knowledge increased after applying the program.Conclusions: The study confirmed the effectiveness of cardiac rehabilitation instructional program on patients’ knowledge and health-related quality of life and there was significant positive relationship between HRQoL and patient’s sociodemographic and clinical characteristics.Recommendations: The study recommends the application of current CRP within Iraqi cardiac hospitals and centers and the need for further studies on more representative sample.